2005
DOI: 10.1081/jas-200067536
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility Test in the Early Stages of Bronchial Asthma

Abstract: In the early stages of bronchial asthma, it is frequent to find subjects with a positive history and an FEV 1 or FEV 1 /FVC > 80% of the predicted value. This study investigated if the test of reversibility showed a reversible airway obstruction (RAO) in 291 subjects with the above clinical and functional features. Forced expiratory volume in 1 second (FEV 1 ), forced vital capacity (FVC), and expiratory flows (PEF, MEF 50 , FEF 25 -75 ) were registered before and 20 minutes after salbutamol administration (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Epidemiological studies show that asthma is usually underdiagnosed, and consequently, not adequately treated (20). In part, this could be due to the high number of subjects who tolerate respiratory symptoms for a long time (21).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies show that asthma is usually underdiagnosed, and consequently, not adequately treated (20). In part, this could be due to the high number of subjects who tolerate respiratory symptoms for a long time (21).…”
Section: Discussionmentioning
confidence: 99%
“…As a side effect of chemotherapy, the destruction of bone marrow structure is observed, affecting the production of new blood cells and therefore reducing white blood cell counts. Obviously, there is a need for new drugs with limited toxicity toward hematopoiesis. Our results showed that only monocytes are susceptible to QB, while lymphocytes were only moderately affected, and only by very high QB doses (>65 μmol/L).…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of the response to broncho-dilating agents was significantly higher among subjects with lower baseline FEV 1 values, representing accentuation of increased bronchial tone or mild airway obstruction. Similarly, Mariotta et al (12) have suggested to perform reversibility tests in all subjects with symptoms indicative of asthma even if their spirometry is "normal" because in a considerable number of cases reversibility confirmed the diagnosis. A similar report by Yurdakul demonstrated high correlation between the results of the reversibility and the presence asthma (13).…”
Section: Discussionmentioning
confidence: 97%